2023
DOI: 10.3390/bs13030225
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Organizational Justice, Workload, and Emotional Regulation among Medical and Non-Medical Personnel Working in Romanian Healthcare Units

Abstract: Background and objectives: The goal of this study was to evaluate the levels of organizational justice, emotional regulation, and workload associated with the level of burnout experienced in medical and non-medical staff from public and private medical units. Materials and Methods: A cross-sectional study was conducted on a sample of 230 healthcare professionals, including 139 medical personnel and 91 non-medical staff respondents. The collected socio-demographic and organizational data and psychological tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Medical personnel experience a higher level of organizational justice and personal accomplishment than non-medical personnel. These results are similar to previous research that revealed a higher level in the case of these dimensions for medical personnel [ 34 ]. A higher wellbeing score for medical staff was also recorded.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Medical personnel experience a higher level of organizational justice and personal accomplishment than non-medical personnel. These results are similar to previous research that revealed a higher level in the case of these dimensions for medical personnel [ 34 ]. A higher wellbeing score for medical staff was also recorded.…”
Section: Discussionsupporting
confidence: 92%
“…Although on January 1, 2023, staff categories assimilated to administrative staff benefited from salary increases of 10%, these increases appeared insufficient against the background of still-high inflation [40] and salary inequities generated over time for this category of staff. Given that doctors and nurses are more professionally fulfilled and experienced significantly higher organizational justice, while administrative staff experienced significantly more EE and D, it seems that this finding is congruent with those of Maslach et al [2] who discovered that a feeling of inequity can eventually determine professional burnout, inequity often being felt against the background of workload [34] or financial considerations [2].…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the research focuses upon patient-facing employees and not non-patient-facing employees. Claponea and Iorga (2023) analyze burnout and perceptions of organizational justice among medical and non-medical employees but do not analyze other aspects of OC, such as organizational support.…”
Section: The Relationship Between Organizational Culture and Burn Outmentioning
confidence: 99%
“…Therefore, further research is needed. (Claponea& Iorga, 2023). Some studies combine OC and burnout questions, such as Roth et al (2021).…”
Section: The Relationship Between Organizational Culture and Burn Outmentioning
confidence: 99%
“…6 In addition, the coronavirus disease 2019 (COVID-19) pandemic contributed substantially to heightened physician burnout globally. 7,8 Although the prevalence of burnout among rheumatologists is not well reported, recent investigations suggest it is substantial, at around 50%. In 2019 and prior to the COVID-19 pandemic, a survey of 128 rheumatologists demonstrated that at least 50% had burnout in 1 or more domains of the Maslach Burnout Index (MBI).…”
mentioning
confidence: 99%